Efficacy, effectiveness, and safety of herpes zoster vaccine in the immunocompetent and immunocompromised subjects: A systematic review and network meta-analysis - Xia, Yue; Zhang, Xue; Zhang, Liuren; Fu, Chuanxi (Frontiers in Immunology, 2022)
Objective: To investigate the efficacy, effectiveness and safety of recombinant zoster vaccine (RZV) and zoster vaccine live (ZVL) in immunocompetent and immunocompromised subjects. Methods: Data sources: PubMed, EMBASE, Cochrane Library, and Web of Science databases (up to Jan 2022) were searched to identify English articles. Search terms included randomized controlled trials (RCTs), observational studies, herpes zoster, RZV, ZVL. Study Selection: Only randomized controlled trials (RCTs) evaluating vaccine efficacy and safety and observational studies assessing vaccine effectiveness (after a vaccine was approved for marketing) were included. Data Extraction: Two researchers independently screened the literature, extracted the data, and checked the each other results. Results: Seventeen RCTs and 19 cohort studies were included. Among immunocompetent subjects, RZV was superior to ZVL at wide intervals (relative vaccine efficacy: 84%, 95% CI: 53%–95%; relative vaccine effectiveness: 49%, 95% CI: 21%–67%), across genders and subjects aged ≥ 60 years. Among immunocompromised subjects, RZV was superior to placebo in terms of vaccine efficacy (60%, 95% CI: 49%–69%). There was no difference between ZVL and placebo in those with selected immunosuppressive conditions. RZV was 45% (95% CI: 30%–59%) superior to ZVL in real-world practice. Compared with placebo, adverse events related to RZV were primarily related to injection-site and systemic, and RZV did not increase the risk of serious adverse events (SAEs) or death. There was no difference in the incidence of adverse events between groups with and without immunosuppression. Conclusions: Both RZV and ZVL can reduce the risk of herpes zoster in both immunocompetent and immunocompromised subjects. RZV was well-tolerated in the study population and demonstrated stronger protection than ZVL. Protocol registration: Prospero CRD42022310495.